Niketche: a literary performance of freedom - Shimbo, Renata Vaz (2018)
In this article we analyze the novel Niketche: uma história de poligamia by the Mozambican writer Paulina Chiziane, with the purpose of demonstrating the subversion of the niketche dance ritual as a literary performance through the subjectivation of the female voice in Mozambique. The cultural layout, marked by the country’s geographical differences, shapes the relationships that Mozambican women establish with their bodies. In turn, the Portuguese language, an element of domination, creates the background in which the narrative is sewn. Together, they form the scenario evoked by Chiziane to stage a female narrative about the act of being a woman in Mozambique. ---DOI: http://dx.doi.org/10.22409/abriluff2018n21a527.